2008
DOI: 10.1016/j.vaccine.2008.04.070
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Lactobacillus acidophilus enhances the immunogenicity of an oral rotavirus vaccine in gnotobiotic pigs

Abstract: We evaluated virus-specific B and T cell responses induced by the attenuated Wa (P1A[8]G1) human rotavirus (AttHRV) oral 2-dose vaccine with or without Lactobacillus acidophilus (LA) colonization in neonatal gnotobiotic (Gn) pigs. The AttHRV vaccinated and LA-fed pigs had a significantly higher magnitude of HRV-specific IFN-gamma producing CD8+ T cell responses in ileum and spleen, IgA and IgG antibody-secreting cell responses in ileum, and serum IgM, IgA and IgG antibody and virus neutralizing antibody titers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(109 citation statements)
references
References 30 publications
7
100
0
1
Order By: Relevance
“…Although these two strains were not able to reduce virus replication into IPEC-J2 cells, they could differently modulate cellular immune response. Indeed, LA treatment prior to RV infection significantly increased virus-induced IL-6 response, consistent with the adjuvant effect of this strain, in potentiating immunogenicity of an oral RV vaccine in a gnotobiotic pig model (Zhang et al 2008). On the contrary, LGG treatment post-RV infection downregulated the IL-6 response, confirming the well documented anti-inflammatory effect of LGG.…”
Section: Probiotics Used In Pig Intestinal Cells Challenged With Virusessupporting
confidence: 77%
“…Although these two strains were not able to reduce virus replication into IPEC-J2 cells, they could differently modulate cellular immune response. Indeed, LA treatment prior to RV infection significantly increased virus-induced IL-6 response, consistent with the adjuvant effect of this strain, in potentiating immunogenicity of an oral RV vaccine in a gnotobiotic pig model (Zhang et al 2008). On the contrary, LGG treatment post-RV infection downregulated the IL-6 response, confirming the well documented anti-inflammatory effect of LGG.…”
Section: Probiotics Used In Pig Intestinal Cells Challenged With Virusessupporting
confidence: 77%
“…The homologous/heterologous virus-neutralizing (VN) antibody titers against PRV G9P [13], HRV Wa G1P [8], PRV OSU G5P [7], and PRV Gottfried G4P [6] in convalescent-phase/hyperimmune sera were determined by a fluorescent-focus neutralization (FFN) test, as previously described (43). The VN titer was expressed as the reciprocal of the highest dilution of serum that reduced the number of infected-cell foci by 80%.…”
Section: Methodsmentioning
confidence: 99%
“…35,63 Only one small RRV-TV study in Finnish infants randomized to lactobacillus GG has been able to demonstrate an improvement in IgA seroconversion. 35 No other study has demonstrated improved correlates of rotavirus immunity associated with adjuvant use.…”
Section: Rotavirus Vaccine Adjuvantsmentioning
confidence: 99%